Sinergitas Bumdes dalam Manajemen Pengelolaan Desa Wisata Menuju Pariwisata Berkelanjutan - Aeni, Ida Nur; Mahmud, Amir; Susilowati, Nurdian; Prawitasari, Andhika Bella (Jurnal Abdimas, 2021)
Sustainable development is an issue discussed by the current government apparatus. In the tourism sector also every region began to focus on sustainable tourism Sustainable tourism is an alternative to mass tourism and efforts to increase positive effects and reduce the harmful effects of tourism on local communities and the natural environment. Munding is a village located in Kecamatan Bergas, Kabupaten Semarang, Provinsi Jawa Tengah. Desa Munding has tourism potential including Curug Tirto Wening, Curug Tirto Wati, Bukit Kembar Cemanggal, and Religious Tourism Tomb sheikh syarif. However, the tour has not been entirely appropriately managed, so it requires further management to become a tour with good governance. There are three priority aspects focused on this devotion: human resources, infrastructure, and participation. The solution to human resource problems are done through the socialization of tourism village management and improving the literacy of tourism village development to the local community. Furthermore, the solution to infrastructure problems is done by rejuvenating existing facilities and infrastructure and continuously monitoring facilities and infrastructure. So always maintain it is quality. Meanwhile, the solution to the problem of low participation is done by integrating all elements supporting tourist villages, including village-owned enterprises in the Munding village. Through the assistance, it is expected that Munding village becomes a tourist village with a higher selling value to improve the community's welfare.